Weak Protection of Civil Rights Zina Children in Indonesia - Suryati; Teguh Anindito (Cyber Media Indonesia, 2022)
The position of a child is very important for a family and a country. Children are part of the younger generation, as one of the human resources, as a great potential and a successor to the ideals of the nation. Children must be guaranteed a complete, harmonious, harmonious and balanced physical, mental, social growth. It can even be said that children are a gift that is also a mandate given by Allah SWT to every parent. Children in Article 1 paragraph 1 of Law Number 23 Year 2002 in conjunction with Law Number 35 Year 2014 concerning Child Protection are someone who is not yet 18 years old, including children who are still in the womb. Article 42 of Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 concerning Marriage, regulates that legal children are children born in or as a result of a legal marriage. The purpose of this study was to determine the weaknesses in protecting the civil rights of adultery children in Indonesia. The research specification is descriptive. Primary data collection method through interviews, while secondary data collection is documentative. The data obtained were analyzed qualitatively. Conclusion: The weakness of protecting the civil rights of adultery children in Indonesia is that there are many children who are neglected, the stigma of society, the biological father of adultery children is not responsible, it is rare for families to place adultery children, if there are families who want to accommodate adultery children but the origin of the child is hidden.